Isolamento e seleção de fungos filamentos produtores de xilanases e celulases utilizando resíduos agroindustriais - Senna, Sirlene do Nascimento [UNESP] (2014)
One hundred forty-eight mesophilic and thermophilic fungal strains were isolated from samples of soil and decomposing organic matter from Cerrado in the state of Mato Grosso do Sul. These strains have had their capacity for growth at 35 °C and 45 °C analyzed in culture medium containing corn straw as the carbon source. Sixty-six fungi, growing at 45 °C, were selected for enzyme production testing. The most of the isolated strains produced xylanase and cellulase (CMCase and avicelase) by solid state fermentation (SSF), initially using wheat bran as substrate. Subsequently, studies of the effect of carbon source and enzyme production profile were performed using different substrates: wheat bran, sugar cane bagasse, sawdust, corn cobs and mixtures in a 1:1 ratio. The highest CMCase production, 18 U/g, was produced by fungi Penicillium sp 1IP4-A2 in wheat bran, after 48 hours of cultivation. The highest avicelase production, 13.1 U/g, and xylanase, 370 U/g, were obtained by fungi Aspergillus sp 1IP2B1, in wheat bran and corn cob, after 24 hours and 96 hours of culture on solid fermentation, respectively. The xylanase produced by fungi Aspergillus sp 1IP2B1 showed maximum activity at 55 °C at pH 5.5 and it was stable up to 55 °C